Exploring the Cultural Space of the Lamalera Fishing Community in Lembata Island, Indonesia - Yoseph Yapi Taum; I. Praptomo Baryadi (Randwick International of Social Science Journal, 2024)
This research aims to examine the sea as a cultural space within the context of the Lamalera fishing community on Lembata Island. There exists a complex relationship between humans and the marine environment, encompassing cultural, economic, social, political, and spiritual aspects. The study reveals the maritime cultural heritage and cultural practices that have evolved around the sea, including myths, customs, fishing traditions, maritime trade, and the utilization of marine resources. Additionally, the research identifies the role of the sea in shaping the cultural identity of the Lamalera community, including livelihoods, beliefs, and unique cultural practices. This field study employs an interdisciplinary approach encompassing history, anthropology, sociology, and culture. Viewing the sea as a cultural space, the study unveils three cultural domains: mental facts, social facts, and artifacts. The results indicate that the Lamalera fishing community is a maritime society, where the entire cultural and spiritual identity is shaped by the sea as a cultural space.